Modified adhesive layer for manufacturing FPC (Flexible Printed Circuit) and preparation method of modified adhesive layer
By using a modified adhesive layer preparation method during the FPC production process, UV photocuring resin, crosslinking resin composition and modified filler are added, the heat resistance and adhesion of existing adhesives during high-temperature laser process are solved. The problem of insufficient results enables higher high temperature resistance and peeling force, reducing the probability of residual glue.
Patent Information
- Application Number
- CN202510016560.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-06
AI Technical Summary
During the production process of FPC, existing adhesives lack heat resistance and adhesion during high-temperature laser, resulting in residual adhesive adhesion on copper foil, affecting production yield.
By adopting a method of preparing a modified glue layer, a polymer network structure resin is formed by adding UV photocuring resin, a crosslinking resin composition and a modified filler to the solvent-based pressure-sensitive adhesive, and UV light and high temperature maturation are carried out. Improve the high temperature resistance and peeling force of the glue layer.
It significantly improves the high temperature resistance and peeling force of the glue layer, reduces the probability of residual glue, and improves the yield of production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a modified adhesive layer used for making FPC and a preparation method thereof. Background Art
[0002] FPC is a flexible circuit board made of polyester film or polyimide film as the substrate, copper foil is plated on it to form a conductive pattern, and then processed by chemical etching, drilling and stamping. Compared with traditional rigid circuit boards, it has higher flexibility and plasticity. FPC is mainly composed of substrate, copper foil, surface protection layer and connector. Among them, the substrate is the main part of the entire FPC, and polyester film or polyimide film can be selected as the substrate; copper foil is the conductive layer, and the conductor pattern is printed on the copper foil by chemical methods; the surface protection layer can be selected to cover the copper foil for protection; in the front-end production process of FPC, in order to improve production efficiency, the current FPC board factory usually temporarily bonds two layers of copper foil together in a back-to-back manner, and then the double-sided copper foil is subjected to laser, Desmear, black hole, pressed dry film, exposure, development, film removal and other processes. In the above-described processes, the laser process has high temperature and the laser surface is very small. The waste residue after laser can usually be removed by desmear. The copper residue and glue residue can be removed. If there is excess glue residue that is not removed, then these glue residues will adhere to the copper foil, thereby causing a circuit break when etching the circuit later.
[0003] As a thin PET double-sided adhesive auxiliary material used in the first copper foil double-sided lamination process in FPC manufacturing, it is involved in the lamination of copper foil and the high-temperature laser punching, high-temperature acid washing, alkaline washing and other cleaning and subsequent hot pressing processes. Therefore, in this process, the double-sided adhesive is sandwiched between two copper foils. When passing through the laser process, the laser will penetrate the copper foil layer and the double-sided tape layer. During the laser process, the laser will instantly reach a high temperature of thousands of degrees Celsius. At this time, the copper foil and the inner layer of double-sided adhesive will melt under the action of the high-temperature laser. Since the copper foil itself is a non-sticky material, the copper slag removed by the laser will be high-temperature. The double-sided adhesive tape sandwiched between them will also melt at high temperatures. The double-sided adhesive tape structure is acrylic pressure-sensitive adhesive coated on both sides of the PET substrate. Because the pressure-sensitive adhesive is a high-molecular acrylic polymer, it has a certain viscosity at room temperature. Therefore, after laser irradiation, if the heat resistance of the pressure-sensitive adhesive polymer is insufficient or the adhesion between the colloid and the PET substrate is insufficient, then after high temperature, the adhesive removed by the laser and the adhesive not removed by the laser will adhere to each other. When peeled off at too high a temperature in the later stage, the residual adhesive will be transferred to the copper foil surface, which will cause the residual adhesive to break when etching the circuit in the later stage, thus affecting the overall production yield. Therefore, the adhesive layers on both sides of the adhesive material involved in this process must have good heat resistance and cohesive strength. The adhesive layer commonly used in such applications is solvent-based acrylic adhesive, and the molecular weight of acrylic adhesive made by the solvent method is generally less than 1 million. Although the molecular weight of adhesives at this molecular weight level can be greatly increased by adding cross-linking agents, the cross-linking density is relatively small. Therefore, when subjected to ultra-high temperature radium, the molecular chain melts and shifts due to insufficient polymer rigidity, resulting in local residual glue. This makes the overall rigidity of the adhesive layer insufficient, resulting in residual glue at the edge of the laser contact area during high-temperature laser irradiation, which leads to poor subsequent production lines.
[0004] At present, different manufacturers have chosen different methods to solve such problems: 1. For example, Suzhou Wule also has products for such applications. Wule uses the coating treatment of the middle layer PET of the tape to greatly enhance the bonding force between the adhesive layer and the PET layer, so that it can also meet the customer's use requirements to a certain extent. This method requires the PET film to be double-sided coated in advance. The commonly used coatings are generally polyurethane coatings, acrylic coatings and polyester coatings. After the coating treatment, the double-sided coating of the adhesive layer is carried out. In this way, the coated PET surface can have excellent adhesion with the adhesive layer. Even if there is residual glue after laser treatment, the residual glue part will have better adhesion with PET. Most of the residual glue will not be transferred to the copper foil, thereby reducing the proportion of residual glue transfer. 2. In addition, some manufacturers have made adjustments to the production process parameters, such as adjusting the temperature parameters of coating and drying, and the aging method, in order to make the cross-linking degree of the adhesive layer more uniform, thereby reducing the residual glue caused by uneven cross-linking. This method is to control the temperature of each section of the oven during the coating of the adhesive layer, so that the adhesive layer will not react rapidly due to excessive local temperature. In addition, because this tape is a double-sided tape, and both sides are directly coated (the adhesive layer is directly coated on the PET surface), when the second adhesive layer is coated after the first adhesive layer is coated, the previously coated first adhesive layer will enter the oven again and experience high temperature twice, while the second adhesive layer will only experience high temperature once. Therefore, the temperature conditions experienced by the two adhesive layers are very different, resulting in obvious differences in the degree of curing of the two adhesive layers. Therefore, the drying temperature of the two adhesive layers will be adjusted, such as lowering the drying temperature of the first adhesive layer and increasing the drying temperature of the second adhesive layer, and then curing at room temperature after coating is completed. This can greatly reduce the difference in the degree of curing of the double-sided adhesive layers, and after the subsequent room temperature curing, the overall cross-linking uniformity will be greatly enhanced, thereby reducing the proportion of residual adhesive caused by uneven curing and cross-linking of the double-sided adhesive layers.
[0005] Among the two common solutions to the problem of residual glue, the first solution is to prime PET, which has the most obvious effect, but is also the most complicated to operate. First, a suitable primer should be selected to match the adhesive to be coated. In addition, both the front and back sides of PET need to be primed, which adds two processes and the corresponding material and labor costs. In addition, the multiple process operations greatly reduce the production yield. Since the adhesive layer itself has not been fundamentally improved, the reduction in the final residual glue rate is limited. The second solution is to adjust the process conditions during the coating process to improve the uniformity of colloid cross-linking. This method belongs to the adjustment of the process parameter level, requiring the coating process to have high precision of the equipment and extremely high dependence on the production equipment. It is a dedicated line. In addition, due to the different drying temperatures on the front and back sides, the complexity of the coating operation is increased. Moreover, since only the drying temperature and the aging conditions are adjusted, the curing level of the adhesive layer on both sides can indeed be made more uniform, but it also does not effectively improve the rigidity of the adhesive layer, so the final improvement of the residual glue is also relatively limited. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a modified adhesive layer for FPC and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a modified adhesive layer for FPC, the method comprising the following steps: (1) Adding UV light-curing resin, cross-linking resin composition and modified filler to the solvent-based pressure-sensitive adhesive in sequence, and then stirring and mixing evenly; continuing to add photoinitiator, and then continuing to stir evenly under a yellow light lamp; then continuing to add NCO type curing agent or epoxy type curing agent, and continuing to stir evenly under a yellow light lamp to obtain a mixed colloid; (2) Apply the mixed colloid to one side of the PET, and then adhere the colloid surface to the release film and roll it up; (3) Continue to evenly apply the mixed colloid to the other side of the PET, and then after the adhesive surface is attached to the release film, both sides of the PET are irradiated with UV light at the same time, and then the irradiated tape is rolled up; (4) Finally, the rolled double-sided tape is subjected to high temperature curing at 50°C to obtain a modified adhesive layer for FPC production.
[0008] Furthermore, the peel force of the solvent-based pressure-sensitive adhesive is between 500-800 gf.
[0009] Furthermore, the solvent-based pressure-sensitive adhesive adopts one or more of NT-00 (Jiangxi Ta Yi Lai), Y-1510 (Jiaxing Anzuo Chemical), and C-439U (Nanjing Zongyan).
[0010] Furthermore, the mass percentage of the solvent-based pressure-sensitive adhesive in the mixed colloid is 30-50wt%.
[0011] The preparation method of the cross-linked resin composition comprises: mixing 40-46 parts by mass of cyanate ester and 60-70 parts by mass of prepolymer, stirring at 62-67° C. for 15-20 minutes, adding 1-3 parts by mass of cobalt oxalate and 15-20 parts by mass of N-vinyl pyrrolidone, stirring evenly, then adding 2-5 parts by mass of 1-hydroxycyclohexyl phenyl ketone, stirring evenly, and vacuuming for 10 minutes to obtain the cross-linked resin composition.
[0012] Furthermore, the cyanate ester is selected from at least one of bisphenol A cyanate ester, dicyclopentadiene cyanate ester, and tetramethyl bisphenol F cyanate ester.
[0013] Furthermore, the cyanate ester is bisphenol A type cyanate ester, dicyclopentadiene type cyanate ester, and tetramethyl bisphenol F type cyanate ester in a mass ratio of 1:1.3-1.5:0.4-0.8.
[0014] Bisphenol A cyanate ester, CAS number: 3053-88-4.
[0015] Dicyclopentadiene cyanate ester, CAS number: 68322-12-8.
[0016] Tetramethyl bisphenol F cyanate, CAS: 101657-77-6.
[0017] Furthermore, the prepolymer is selected from at least one of polyurethane acrylate, epoxy acrylate, and isocyanuric acid acrylate.
[0018] Furthermore, the prepolymer is polyurethane acrylate, epoxy acrylate and isocyanuric acid acrylate in a mass ratio of 1.6-1.8:1:0.2-0.5.
[0019] The polyurethane acrylate was purchased from EBECRYL 8213 of Allnex.
[0020] The epoxy acrylate was purchased from Sartomer Products, model CN120NS.
[0021] The isocyanuric acid acrylate was purchased from Sartomer, model SR368NS.
[0022] Furthermore, the mass percentage of the cross-linked resin composition in the mixed colloid is 12-15wt%.
[0023] The present invention adopts chemical modification of the adhesive layer, and adds a UV curable resin to the original solvent-based pressure-sensitive adhesive, thereby improving the adhesion between the adhesive layer and the steel plate and increasing the peeling force from the steel plate. This UV curable resin can be perfectly dissolved in the solvent and evenly dispersed in the solvent-based pressure-sensitive adhesive. The adhesive layer with the UV curable resin can be evenly coated on the surface of the PET substrate by coating. After the solvent in the adhesive layer is evaporated after high-temperature drying in an oven, a UV illumination process is then performed, so that the UV curable resin dissolved therein can react and cross-link quickly, thereby greatly improving the cross-linking degree of the colloid, while the original solvent-based pressure-sensitive adhesive retains good pressure sensitivity to meet the viscosity required for bonding. However, under this condition, the peeling force between the adhesive layer and the PI film is not ideal.
[0024] The present invention further adds a cross-linked resin composition to improve the peeling force between the adhesive layer and the PI film. In the system of the present invention, UV light-curable resin and the cross-linked resin composition are added simultaneously, and the photocuring interpenetration forms a polymer network structure resin, which improves the peeling force between the adhesive layer and the PI film and improves the high temperature resistance of the adhesive layer.
[0025] Furthermore, the preparation method of the modified filler is: (1) Mixing silicon dioxide, yttrium oxide and mica powder in a mass ratio of 1:1.3-1.5:0.4-0.7 to obtain a mixed filler; (2) Disperse 10 parts by weight of the mixed filler in 60-70 parts by weight of a 50-60 wt% ethanol aqueous solution, add 0.1-0.3 parts by weight of a silane coupling agent KH550 and 0.4-0.6 parts by weight of hexadecyltrimethylammonium bromide, react at 60-65° C. for 4-6 hours, centrifuge and dry to obtain a modified filler.
[0026] Furthermore, the mica powder is mica powder with a D90 particle size of 6 μm. Shijiazhuang Chenxing Industrial Co., Ltd. The average particle size of silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Ningbo Jinlei Nanomaterials Technology Co., Ltd. The particle size of yttrium oxide is 20-30nm, and the average specific surface area is 61m 2 / g. Ningbo Jinlei Nanomaterial Technology Co., Ltd.
[0027] The present invention attempts to add fillers to the adhesive layer system to improve the effect of no residual glue after high-temperature baking of the adhesive layer, but the effect is not ideal. The present invention improves the effect of no residual glue after high-temperature baking of the adhesive layer by using mixed fillers with specific parameters and adding them to the system of the present invention after modification. The modified mixed filler has better compatibility with other components in the system of the present invention. At the same time, the specific parameters of silica, yttrium oxide and mica powder can adjust the rheological properties of the adhesive layer, which helps to achieve better coating performance during the application process and form a more uniform adhesive layer, thereby reducing residues during peeling.
[0028] Furthermore, the mass percentage of the modified filler in the mixed colloid is 5-7wt%.
[0029] Furthermore, the UV light-curing resin is selected from one of PRO32284 (Sartomer), GD83-02 (Sanhe Chemical), GD83-04 (Sanhe Chemical), and 6151 (Showa Chemical, Japan).
[0030] Furthermore, the mass percentage of the UV light-curing resin in the mixed colloid is 30-50%.
[0031] Furthermore, the photoinitiator is one or more of IRGACURE 184, DAROCUR 1173, IRGACURE 127, IRGACURE 2959, and LUCIRIN TPO.
[0032] Furthermore, the mass percentage of the photoinitiator in the mixed colloid is 0.5-5%.
[0033] Furthermore, the NCO type curing agent is any one or more of an adduct of toluene diisocyanate and trimethylolpropane, toluene diisocyanate trimer, hexamethylene diisocyanate trimer, and hexamethylene diisocyanate polymer.
[0034] Furthermore, the mass percentage of the NCO type curing agent in the mixed colloid is 0.5-2%.
[0035] Furthermore, the epoxy type curing agent is any one or more of HY-H024 (Huiya New Materials), HY-H026 (Huiya New Materials), NE-100C (Japan Soken), NE-100X (Japan Soken), and Y-202 (Jiaxing Anzuo).
[0036] Furthermore, the mass percentage of the epoxy type curing agent in the mixed colloid is 0.5-2%.
[0037] Furthermore, the thickness of PET is selected from 4 μm, 6 μm, 10 μm, 12 μm, and 25 μm.
[0038] Furthermore, the coating thickness of the mixed colloid on any one side of the PET is 3-10 μm.
[0039] Furthermore, the light wavelength of the UV lamp is any wavelength between 285nm-365nm.
[0040] The present invention also provides a modified adhesive layer for FPC prepared by the above preparation method.
[0041] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention adopts chemical modification of the adhesive layer, and adds a UV curable resin to the original solvent-based pressure-sensitive adhesive. This UV curable resin can be perfectly dissolved in the solvent and evenly dispersed in the solvent-based pressure-sensitive adhesive. In this way, the adhesive layer with the UV curable resin can be evenly coated on the surface of the PET substrate by a traditional coating method. After the solvent in the adhesive layer is evaporated by high-temperature drying in an oven, a UV irradiation process is performed, so that the UV curable resin dissolved therein can react and cross-link quickly, thereby greatly improving the cross-linking degree of the colloid, and the original solvent-based pressure-sensitive adhesive retains good pressure sensitivity to meet the viscosity required for bonding. Therefore, this method only adds a UV irradiation process at the back end of the bonding process in terms of the operating process, and the production process and efficiency are still retained. The method and efficiency are not affected, thereby solving the contradiction between the incompatibility of the rigidity and viscosity of the adhesive layer from the perspective of the adhesive layer itself, greatly improving the rigidity of the adhesive layer, and greatly reducing the probability of residual adhesive.
[0042] 2. In the system of the present invention, UV light-curing resin and cross-linking resin composition are added simultaneously, and the light-curing interpenetration forms a polymer network structure resin, thereby improving the peeling force between the adhesive layer and the PI film and improving the high temperature resistance of the adhesive layer.
[0043] 3. The present invention improves the effect of no residual glue after high-temperature baking of the glue layer by using mixed fillers with specific parameters and adding them into the system of the present invention after modification. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment provides a modified adhesive layer for FPC, and the preparation method includes the following steps: (1) Add UV light-curing resin, cross-linking resin composition and modified filler to the solvent-based pressure-sensitive adhesive in sequence, and then stir and mix them evenly; continue to add photoinitiator, and then continue to stir evenly under yellow light; then continue to add NCO type curing agent, and continue to stir evenly under yellow light to obtain a mixed colloid; (2) Apply the mixed colloid to one side of the PET, and then adhere the colloid surface to the release film and roll it up; (3) Continue to evenly apply the mixed colloid to the other side of the PET, and then after the adhesive surface is attached to the release film, both sides of the PET are irradiated with UV light at the same time, and then the irradiated tape is rolled up; (4) Finally, the rolled double-sided tape is subjected to high temperature curing at 50°C to obtain a modified adhesive layer for FPC production.
[0047] The solvent-based pressure-sensitive adhesive used is NT-00 (Jiangxi Ta Yi Lai).
[0048] The preparation method of the cross-linked resin composition is as follows: 43 parts by mass of cyanate ester and 64 parts by mass of prepolymer are mixed, stirred at 65° C. for 18 minutes, 2 parts by mass of cobalt oxalate and 17 parts by mass of N-vinyl pyrrolidone are added, stirred evenly, and then 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone are added, stirred evenly, and vacuumed for 10 minutes to obtain the cross-linked resin composition.
[0049] The cyanate esters are bisphenol A type cyanate ester, dicyclopentadiene type cyanate ester and tetramethyl bisphenol F type cyanate ester in a mass ratio of 1:1.4:0.6.
[0050] The prepolymer is polyurethane acrylate, epoxy acrylate and isocyanuric acid acrylate in a mass ratio of 1.7:1:0.4.
[0051] The polyurethane acrylate was purchased from EBECRYL 8213 of Allnex.
[0052] The epoxy acrylate was purchased from Sartomer Products, model CN120NS.
[0053] The isocyanuric acid acrylate was purchased from Sartomer, model SR368NS.
[0054] The preparation method of the modified filler is: (1) mixing silicon dioxide, yttrium oxide and mica powder in a mass ratio of 1:1.4:0.5 to obtain a mixed filler; (2) 10 parts by mass of the mixed filler were dispersed in 65 parts by mass of a 55 wt% ethanol aqueous solution, 0.2 parts by mass of a silane coupling agent KH550 and 0.5 parts by mass of hexadecyltrimethylammonium bromide were added, the mixture was reacted at 62° C. for 5 h, centrifuged and dried to obtain a modified filler.
[0055] The mica powder is mica powder with a D90 particle size of 6 μm. Shijiazhuang Chenxing Industrial Co., Ltd. The average particle size of silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Ningbo Jinlei Nanomaterials Technology Co., Ltd. The particle size of yttrium oxide is 20-30nm, and the average specific surface area is 61m 2 / g. Ningbo Jinlei Nanomaterial Technology Co., Ltd.
[0056] The UV light curing resin was selected from PRO32284 (Sartomer).
[0057] The photoinitiator was IRGACURE 184 (BASF).
[0058] The NCO type curing agent is toluene diisocyanate trimer (Covestro).
[0059] The mass percentage of solvent-based pressure-sensitive adhesive in the mixed colloid is 36wt%. The mass percentage of the cross-linked resin composition in the mixed colloid is 14wt%. The mass percentage of the modified filler in the mixed colloid is 6wt%. The mass percentage of the UV light-curing resin in the mixed colloid is 40%. The mass percentage of the photoinitiator in the mixed colloid is 3%. The mass percentage of the NCO type curing agent in the mixed colloid is 1%.
[0060] The thickness of PET is 10 μm.
[0061] The coating thickness of the mixed colloid on either side of PET is 5 μm.
[0062] The wavelength of UV light is 365nm.
[0063] Example 2
[0064] This embodiment provides a modified adhesive layer for FPC, and the preparation method includes the following steps: (1) Adding UV light-curing resin, cross-linking resin composition and modified filler to the solvent-based pressure-sensitive adhesive in sequence, and then stirring and mixing evenly; continuing to add photoinitiator, and then continuing to stir evenly under a yellow light lamp; then continuing to add epoxy type curing agent, and continuing to stir evenly under a yellow light lamp to obtain a mixed colloid; (2) Apply the mixed colloid to one side of the PET, and then adhere the colloid surface to the release film and roll it up; (3) Continue to evenly apply the mixed colloid to the other side of the PET, and then after the adhesive surface is attached to the release film, both sides of the PET are irradiated with UV light at the same time, and then the irradiated tape is rolled up; (4) Finally, the rolled double-sided tape is subjected to high temperature curing at 50°C to obtain a modified adhesive layer for FPC production.
[0065] The solvent-based pressure-sensitive adhesive used was Y-1510 (Jiaxing Anzuo Chemical).
[0066] The preparation method of the cross-linked resin composition is as follows: 40 parts by mass of cyanate ester and 70 parts by mass of prepolymer are mixed, stirred at 62° C. for 15 minutes, 1 part by mass of cobalt oxalate and 20 parts by mass of N-vinyl pyrrolidone are added, stirred evenly, and then 2 parts by mass of 1-hydroxycyclohexyl phenyl ketone are added, stirred evenly, and vacuumed for 10 minutes to obtain the cross-linked resin composition.
[0067] The cyanate esters are bisphenol A type cyanate ester, dicyclopentadiene type cyanate ester and tetramethyl bisphenol F type cyanate ester in a mass ratio of 1:1.3:0.8.
[0068] The prepolymer is polyurethane acrylate, epoxy acrylate and isocyanuric acid acrylate in a mass ratio of 1.6:1:0.5.
[0069] The polyurethane acrylate was purchased from EBECRYL 8213 of Allnex.
[0070] The epoxy acrylate was purchased from Sartomer Products, model CN120NS.
[0071] The isocyanuric acid acrylate was purchased from Sartomer, model SR368NS.
[0072] The preparation method of the modified filler is: (1) mixing silicon dioxide, yttrium oxide and mica powder in a mass ratio of 1:1.3:0.7 to obtain a mixed filler; (2) Disperse 10 parts by mass of the mixed filler in 60 parts by mass of a 60 wt% ethanol aqueous solution, add 0.1 parts by mass of a silane coupling agent KH550 and 0.6 parts by mass of hexadecyltrimethylammonium bromide, react at 60° C. for 6 h, centrifuge and dry to obtain a modified filler.
[0073] The mica powder is mica powder with a D90 particle size of 6 μm. Shijiazhuang Chenxing Industrial Co., Ltd. The average particle size of silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g. Ningbo Jinlei Nanomaterials Technology Co., Ltd. The particle size of yttrium oxide is 20-30nm, and the average specific surface area is 61m 2 / g. Ningbo Jinlei Nanomaterial Technology Co., Ltd.
[0074] The UV light curing resin was selected from GD83-02 (Sanhe Chemical).
[0075] The photoinitiator was DAROCUR 1173 (BASF).
[0076] The epoxy type curing agent is HY-H024 (Huiya New Materials).
[0077] The mass percentage of the solvent-based pressure-sensitive adhesive in the mixed colloid is 44.5 wt%. The mass percentage of the cross-linked resin composition in the mixed colloid is 15 wt%. The mass percentage of the modified filler in the mixed colloid is 5 wt%. The mass percentage of the UV light-curing resin in the mixed colloid is 30%. The mass percentage of the photoinitiator in the mixed colloid is 5%. The mass percentage of the epoxy type curing agent in the mixed colloid is 0.5%.
[0078] The thickness of PET is 10 μm.
[0079] The coating thickness of the mixed colloid on either side of PET is 5 μm.
[0080] The wavelength of UV light is 365nm.
[0081] Comparative Example 1 The difference between this comparative example and Example 1 is that the mass percentage of the cross-linked resin composition in the mixed colloid is 30wt%, and the mass percentage of the UV light-curable resin in the mixed colloid is 15%.
[0082] Comparative Example 2 The difference between this comparative example and Example 1 is that the cyanate ester is bisphenol A type cyanate ester, dicyclopentadiene type cyanate ester and tetramethyl bisphenol F type cyanate ester in a mass ratio of 1:1:1.
[0083] Comparative Example 3 The difference between this comparative example and Example 1 is that the prepolymer is polyurethane acrylate, epoxy acrylate and isocyanuric acid acrylate in a mass ratio of 1:1:1.
[0084] The polyurethane acrylate was purchased from EBECRYL 8213 of Allnex.
[0085] The epoxy acrylate was purchased from Sartomer Products, model CN120NS.
[0086] The isocyanuric acid acrylate was purchased from Sartomer, model SR368NS.
[0087] Comparative Example 4 The difference between this comparative example and Example 1 is that the polyurethane acrylate is a Sartomer product, model CN9001NS.
[0088] The epoxy acrylate was purchased from Sartomer Products, model number CN104NS.
[0089] The isocyanuric acid type acrylate was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd., tris(2-acryloyloxyethyl)isocyanurate.
[0090] Comparative Example 5 The difference between this comparative example and Example 1 is that silicon dioxide, yttrium oxide and mica powder are mixed in a mass ratio of 1:1:1.
[0091] Comparative Example 6 The difference between this comparative example and Example 1 is that the mica powder is mica powder with a D90 particle size of 20 μm. Shijiazhuang Chenxing Industrial Co., Ltd. The average particle size of silicon dioxide is 50 nm and the average specific surface area is 210 m 2 / g. Ningbo Jinlei Nanomaterials Technology Co., Ltd. The particle size of yttrium oxide is 30-70nm, and the average specific surface area is 53m 2 / g. Ningbo Jinlei Nanomaterial Technology Co., Ltd.
[0092] Performance Testing The performance tests were performed on the modified adhesive layers prepared in Examples 1-2 and Comparative Examples 1-6.
[0093] 1. Refer to GB / T 2792-1998 to determine the peeling force between the modified adhesive layer and the steel plate.
[0094] 2. Refer to GB / T 2792-1998 to measure the peeling force between the modified adhesive layer and the PI film.
[0095] 3. Refer to GB / T 2792-1998 to determine the peeling force of the modified adhesive layer after being attached to the PI film at high temperature.
[0096] 4. The modified adhesive layer is baked at 180℃ for 60 minutes. If there is no debonding, bulging, or bubbles, and there is no residual adhesive or foreign matter after peeling, it is considered qualified. Otherwise, it is considered unqualified.
[0097] The test results are shown in Table 1.
[0098] Table 1 Performance test results
[0099] From the above performance test results, it can be seen that the modified adhesive layers of Examples 1-2 have good adhesion, strong high temperature resistance, and no residual adhesive. In particular, the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect of multiple components.
[0100] However, the comparative examples did not adopt the necessary technical solutions, resulting in that the corresponding performance tests were significantly worse than those of the embodiments. In comparative example 1, the addition amounts of the UV light-curing resin and the cross-linking resin composition were changed, and it can be seen that the viscosity effect decreased, proving that the compounding scheme of the UV light-curing resin and the cross-linking resin composition has an important influence on the stripping effect. In comparative examples 5-6, the modified filler scheme was not used, and it can be seen from the results that there is residual glue after stripping. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0101] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a modified adhesive layer for FPC, characterized in that: The preparation method comprises the following steps: (1) Adding UV light-curing resin, cross-linking resin composition and modified filler to the solvent-based pressure-sensitive adhesive in sequence, and then stirring and mixing evenly; continuing to add photoinitiator, and then continuing to stir evenly under a yellow light lamp; then continuing to add NCO type curing agent or epoxy type curing agent, and continuing to stir evenly under a yellow light lamp to obtain a mixed colloid; The preparation method of the cross-linked resin composition comprises: mixing 40-46 parts by mass of cyanate ester and 60-70 parts by mass of prepolymer, stirring at 62-67° C. for 15-20 minutes, adding 1-3 parts by mass of cobalt oxalate and 15-20 parts by mass of N-vinyl pyrrolidone, stirring evenly, then adding 2-5 parts by mass of 1-hydroxycyclohexyl phenyl ketone, stirring evenly, and evacuating for 10 minutes to obtain the cross-linked resin composition; (2) Apply the mixed colloid to one side of the PET, and then adhere the colloid surface to the release film and roll it up; (3) Continue to evenly apply the mixed colloid to the other side of the PET, and then after the adhesive surface is attached to the release film, both sides of the PET are irradiated with UV light at the same time, and then the irradiated tape is rolled up; (4) Finally, the rolled double-sided tape is subjected to high-temperature aging at 50°C to obtain a modified adhesive layer for FPC production.
2. The method for preparing a modified adhesive layer for FPC according to claim 1, characterized in that: The cyanate ester is selected from at least one of bisphenol A cyanate ester, dicyclopentadiene cyanate ester and tetramethyl bisphenol F cyanate ester.
3. The method for preparing a modified adhesive layer for FPC according to claim 2, characterized in that: The cyanate ester is bisphenol A type cyanate ester, dicyclopentadiene type cyanate ester and tetramethyl bisphenol F type cyanate ester in a mass ratio of 1:1.3-1.5:0.4-0.
8.
4. The method for preparing a modified adhesive layer for FPC according to claim 1, characterized in that: The prepolymer is selected from at least one of polyurethane acrylate, epoxy acrylate and isocyanuric acid acrylate.
5. The method for preparing a modified adhesive layer for FPC according to claim 4, characterized in that: The prepolymer is polyurethane acrylate, epoxy acrylate and isocyanuric acid acrylate in a mass ratio of 1.6-1.8:1:0.2-0.
5.
6. The method for preparing a modified adhesive layer for FPC according to claim 1, characterized in that: The preparation method of the modified filler is: (1) Mixing silicon dioxide, yttrium oxide and mica powder in a mass ratio of 1:1.3-1.5:0.4-0.7 to obtain a mixed filler; (2) Disperse 10 parts by weight of the mixed filler in 60-70 parts by weight of a 50-60 wt% ethanol aqueous solution, add 0.1-0.3 parts by weight of a silane coupling agent KH550 and 0.4-0.6 parts by weight of hexadecyltrimethylammonium bromide, react at 60-65° C. for 4-6 hours, centrifuge and dry to obtain a modified filler.
7. The method for preparing a modified adhesive layer for FPC according to claim 6, characterized in that: The mica powder is mica powder with a D90 particle size of 6 μm; the average particle size of silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g; the particle size of yttrium oxide is 20-30nm, and the average specific surface area is 61m 2 / g.
8. The method for preparing a modified adhesive layer for FPC according to claim 6, characterized in that: The photoinitiator is one or more of IRGACURE 184, DAROCUR 1173, IRGACURE 127, IRGACURE 2959, and LUCIRIN TPO.
9. The method for preparing a modified adhesive layer for FPC according to claim 1, characterized in that: The coating thickness of the mixed colloid on either side of PET is 3-10 μm.
10. A modified adhesive layer for FPC prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-dielectric cyanate adhesive and preparation method thereof
CN106047271A
Raw material composition for preparing light-cured resin, light-cured resin prepared from raw material composition and application of light-cured resin
CN112480324A
Explosion-proof adhesive tape, and preparation method and application thereof
CN113683972A
Resin composition, insulating adhesive film and application thereof
CN118459931A
Resin composition, adhesive film using the same and multilayer printed circuit board
US20050187311A1